Internet y la infancia española con problemas de aprendizaje, de comportamiento y otras discapacidades. - Casado del Río, Miguel Ángel; Garmendia Larrañaga, Maialen; Garitaonandia Garnacho, Carmelo (Revista Latina de Comunicación Social, 2019)
Introduction: This article describes the uses, opportunities and risks faced online by children with learning, and behavioural problems. Methodology: The data we analysed corresponds to 61 children who are part of a 500 person 9-16-year-old sample of Internet users, and either their father or mother. Although the group is relatively heterogeneous, it is assumed that they share a common element that is a situation of vulnerability in both their social and digital environments. Results and conclusions: The evidence shows that these children's lack of digital skills and computer equipment in their homes often makes it difficult for them to complete some of their homework and school tasks, and the parental mediation that they receive is also lower than that received by other children. It has also been noted that these minors visit more frequently pages with inappropriate content, such as pages promoting self-injury or suicide, or those dealing with eating disorders.